Mapping of the active site of glutamate carboxypeptidase II by site-directed mutagenesis - Mlčochová, Petra; Plechanovová, Anna; Bařinka, Cyril; Mahadevan, Daruka; Saldanha, Jose W; Rulíšek, Lubomír; Konvalinka, Jan (The FEBS journal, 2007)
Human glutamate carboxypeptidase II [GCPII (EC 3.4.17.21)] is recognized as a promising pharmacological target for the treatment and imaging of various pathologies, including neurological disorders and prostate cancer. Recently reported crystal structures of GCPII provide structural insight into the organization of the substrate binding cavity and highlight residues implicated in substrate/inhibitor binding in the S1' site of the enzyme. To complement and extend the structural studies, we constructed a model of GCPII in complex with its substrate, N-acetyl-l-aspartyl-l-glutamate, which enabled us to predict additional amino acid residues interacting with the bound substrate, and used site-directed mutagenesis to assess the contribution of individual residues for substrate/inhibitor binding and enzymatic activity of GCPII. We prepared and characterized 12 GCPII mutants targeting the amino acids in the vicinity of substrate/inhibitor binding pockets. The experimental results, together with the molecular modeling, suggest that the amino acid residues delineating the S1' pocket of the enzyme (namely Arg210) contribute primarily to the high affinity binding of GCPII substrates/inhibitors, whereas the residues forming the S1 pocket might be more important for the 'fine-tuning' of GCPII substrate specificity.
Keywords: Kinetics; substrátová specifita; myši; Animals; vztahy mezi strukturou a aktivitou; sekvenční seřazení; Glutamic Acid; Rats; Financing, Organized; antigeny povrchové; Humans; Sequence Alignment; Glutamate Carboxypeptidase II; Antigens, Surface; mutageneze cílená; Mutagenesis, Site-Directed; Models, Molecular; lidé; kyselina glutamová; Mice; zvířata; glutamátkarboxypeptidasa II; kinetika; vazebná místa; Binding Sites; molekulární modely; financování organizované; krysa rodu Rattus; Substrate Specificity; Structure-Activity Relationship